Cutting edge: TNF is essential for mycobacteria-induced MINCLE expression, macrophage activation, and Th17 adjuvanticity - Schick, Judith; Schäfer, Johanna; Alexander, Christian; Dichtl, Stefanie; Murray, Peter J.; Christensen, Dennis; Sorg, Ursula; Pfeffer, Klaus; Schleicher, Ulrike; Lang, Roland (Journal of Immunology, 2020)
TNF blockade is a successful treatment for human autoimmune disorders like rheumatoid arthritis and inflammatory bowel disease yet increases susceptibility to tuberculosis and other infections. The C-type lectin receptors (CLR) MINCLE, MCL, and DECTIN-2 are expressed on myeloid cells and sense mycobacterial cell wall glycolipids. In this study, we show that TNF is sufficient to upregulate MINCLE, MCL, and DECTIN-2 in macrophages. TNF signaling through TNFR1 p55 was required for upregulation of these CLR and for cytokine secretion in macrophages stimulated with the MINCLE ligand trehalose-6,6-dibehenate or infected with Mycobacterium bovis bacillus Calmette-Guérin. The Th17 response to immunization with the MINCLE dependent adjuvant trehalose-6,6-dibehenate was specifically abrogated in TNF-deficient mice and strongly attenuated by TNF blockade with etanercept. Together, interference with production or signaling of TNF antagonized the expression of DECTIN-2 family CLR, thwarting vaccine responses and possibly increasing infection risk.
CRIS-Team Scopus Importer:2020-07-31

Experimental Cutaneous Leishmaniasis: Mouse Models for Resolution of Inflammation Versus Chronicity of Disease - Bogdan, Christian; Debus, Andrea; Sebald, Heidi; Rai, Baplu; Schäfer, Johanna; Obermeyer, Stephanie; Schleicher, Ulrike (Leishmania, 2019)
Experimental cutaneous leishmaniasis of mice is a valuable model to study the immune response to the protozoan pathogen Leishmania and to define mechanisms of parasite control and resolution of inflammation as well as of parasite evasion and chronicity of disease. In addition, over many years Leishmania-infected mice have been successfully used to analyze the function of newly discovered immune cell types, transcription factors, cytokines, and effector mechanisms in vivo. In this chapter we present detailed protocols for the culture, propagation, and inoculation of Leishmania promastigotes, the monitoring of the course of cutaneous infection, the determination of the tissue parasite burden and for the phenotyping of the ensuing immune response. The focus lies on the L. major mouse model, but an overview on other established models of murine cutaneous leishmaniasis is also provided.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Cutaneous leishmaniasis; Leishmania major; Mouse models

TNF is required for upregulation of Mincle expression and adjuvant activity in response to mycobacterial glycolipids. - Schick, J.; Lang, Roland; Schäfer, Johanna; Schleicher, Ulrike (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08